The Impact Model of Marketing Information Systems on Financial Performance of Companies - Kargosha, Majid; Barati Devin , Ali (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The objective of this research is to present a model that demonstrates the efficiency and effectiveness of a company's marketing information system through its connection and impact on financial performance variables in 2018.Methodology: The research method, in terms of nature and content, is of a correlational type and belongs to applied studies. The statistical population of this research consists of 440 individuals, including managers and financial and marketing officials from 20 high-performing companies listed on the Tehran Stock Exchange. Based on the Morgan-Krejcie table, a statistical sample of 205 individuals was selected using stratified random sampling. For data analysis, structural equation modeling and multivariate regression were employed using AMOS and SPSS software.Findings: The research results indicate a significant positive relationship between the marketing information system and financial performance. The model's fitness indices suggest that the proposed model has a suitable fit.Conclusion: Overall, it can be stated that intelligent information systems and marketing research are the only components of the marketing information system that have a positive impact on all financial performance variables of the study. Therefore, it is recommended to pay special attention to the subsystems of intelligent information systems and marketing research to enhance the effectiveness and efficiency of the marketing information system.